Herbert a ormiańska Babcia - Słomińska, Emilia (Slavia Occidentalis, 2015)
The text is an attempt to investiage the impact of Zbigniew Herbert’s Armenian grandmother on his ethical outlook on the world. While in his poetry and memoirs there are only few references to Maria of Bałabans and only one poem is entirely about her, contextual references to his grandmother can be traced in most of Herbert’s works and these further emphasise his moral outlook on the world. Furthermore, family memories also confirm the significance of the Armenian grandmother in Herbert’s private and literary life. A very important element of the relationship which brings together the poet and his grandmother is points he role of multiethnic Lviv with which his family had connections for centuries.